Optimalisasi Sistem Pengadaan Secara Elektronik (SPSE) Untuk Meningkatkan Pengadaan Sarana Dan Prasarana: Studi Pada Lembaga Pertahanan Negara Wilayah Jawa Barat - Dhea Perdana Coenraad (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This study aims to see the effectiveness of the use of the electronic procurement system (SPSE) in one of the state defense institutions in the West Java region. In this study, the samples were members of the state defense agency in the resource section. The sampling technique in this study used Probability Sampling with the cluster sampling method. The sampling technique in this study was to use Probability Sampling with the cluster sampling method. It is collecting data using interview and documentation techniques with the analysis technique using the SWOT analysis technique. This study indicates that the use of the Electronic Procurement System in a state defense institution in the West Java region is still not optimal, including due to inadequate human resource factors so that in its implementation, this SPSE does not use optimally. The lack of knowledge of human resources makes optimization from SPSE this is weak.